Pengembangan Media Website Hybrid Learning berbasis Kemampuan Literasi Digital dalam Pembelajaran Fisika - Tetra Rahayu; Tantri Mayasari; Farida Huriawati (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This research was conducted to: (1) develop hybrid learning website media based on digital literacy skills in physics learning, (2) describe the characteristics of products developed, (3) describe students' responses to the developed media. The device developed in the form of hybrid learning website media based on digital literacy skills in physics learning with the development procedure used is the ADDIE model which consists of five stages: analysis, design, development, implementation and evaluation. Media characteristics of hybrid learning websites based on digital literacy capability, namely the website media developed has been based on the concept of hybrid learning and integrated with the dimensions of digital literacy capabilities. Student responses to hybrid learning website media based on digital literacy ability are still in good condition with a percentage of 79.85%.